In vitro definition of the yeast RNA polymerase I enhancer. - Schultz, M C (1993)
In vitro conditions are reported under which an EcoRI-HpaI fragment of the Saccharomyces cerevisiae ribosomal gene spacer will enhance transcription from an adjacent RNA polymerase I promoter. Enhancement is largely independent of orientation and distance and is proportional to copy number. Mapping experiments reveal that two separate regions of the EcoRI-HpaI fragment are independently capable of promoter stimulation. These regions appear to correspond to elements which have been shown by previous workers to cause enhancement in vivo. Using the detergent Sarkosyl to limit the number of rounds of transcription from each promoter, we found that the degree of enhancement is similar whether one or many rounds of transcription occur. This finding supports a model in which the enhancer increases the number of stable promoter complexes but does not alter the loading of polymerase on an active promoter. Once the stable promoter complex is formed, the enhancer can be physically severed from the promoter with no loss of enhancement. Likewise, the upstream activation region of the promoter can be severed from the core promoter domain once the stable complex has been formed. These results are interpreted to mean that the enhancer functions only to assist stable complex formation and, once that is accomplished, the enhancer is dispensable.